The Effect of Moisturizing Treatment of Wind - Miqdad Haidar Al-Jawadi; Ali Farhan Darwish (Iraqi Journal of Architecture and Planning, 2016)
Wind-catchers in traditional architecture in Iraq were small in dimensions, where their horizontal cross section and their largest section did not exceed 0.20 square meters. AS a result, architects abandoned their use in modern building designs, especially after electric fans made available and adopted in buildings. Due to the importance of natural air on human health and as natural air is rich in refreshing negative ions that artificial ventilation lacks, which is usually charged with positive ions, causing drowsiness and depression. New large wind-catchers of more than 2 square meters in cross section were employed by the author in house design responsive to hot climate at the end of the eighties in Iraq.  Such wind-catchers have proved their efficiency in the provision of natural ventilation and lowering internal temperatures during spring and autumn and summer nights. So came the idea of this research by moisturizing the wind catcher walls to raise the performance in summer.  For this purpose practical study has been done by building Wind catcher lined  with bricks burned at a temperature ranging between  1150 - 750 C at which the capillary action integrated, making the water content moderate. Measurements shows in days of 43o C that the moisturized wind catcher reduces air temperature of space connected to the wind catcher to about 12 Â° C